2021
DOI: 10.4142/jvs.2021.22.e86
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned medium of E17 rat brain cells induced differentiation of primary colony of mice blastocyst into neuron-like cells

Abstract: Background Conditioned medium is the medium obtained from certain cultured cells and contained secretome from the cells. The secretome, which can be in the form of growth factors, cytokines, exosomes, or other proteins secreted by the cells, can induce the differentiation of cells that still have pluripotent or multipotent properties. Objectives This study examined the effects of conditioned medium derived from E17 rat brain cells on cells with pluripotent properties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Rinendyaputri et al (2018) reported that growth factors including bFGF and NGF were present in conditioned medium-mesenchymal stem cells (CM-MSCs), which can prevent neuronal cells from degenerating and promote the differentiation of neural stem/progenitor cells (NPCs) into astrocytes and neurons [16]. CM from neural progenitor cells (NPC) is also reported can stimulate differentiation to astrocytes and neurons and can maintain cell growth [17,18]. showed that the addition of bFGF, EGF, and BDNF to the medium induced the differentiation of rat bone marrow MSCs into neurons and glia and characterized neural markers like A2B5, beta-III-tubulin, PSA-NCAM, and MAP-2) [19].…”
Section: Introductionmentioning
confidence: 99%
“…Rinendyaputri et al (2018) reported that growth factors including bFGF and NGF were present in conditioned medium-mesenchymal stem cells (CM-MSCs), which can prevent neuronal cells from degenerating and promote the differentiation of neural stem/progenitor cells (NPCs) into astrocytes and neurons [16]. CM from neural progenitor cells (NPC) is also reported can stimulate differentiation to astrocytes and neurons and can maintain cell growth [17,18]. showed that the addition of bFGF, EGF, and BDNF to the medium induced the differentiation of rat bone marrow MSCs into neurons and glia and characterized neural markers like A2B5, beta-III-tubulin, PSA-NCAM, and MAP-2) [19].…”
Section: Introductionmentioning
confidence: 99%